Epigenetic Regulation of the Nitric Oxide Pathway, 17-α Hydroxyprogesterone Caproate, and Recurrent Preterm Birth - Manuck, Tracy A.; Smeester, Lisa; Martin, Elizabeth M.; Tomlinson, Martha S.; Smith, Christina; Varner, Michael W.; Fry, Rebecca C. (American Journal of Perinatology, 2018)
Objective We sought to evaluate nitric oxide pathway placental gene expression and the epigenome (CpG methylation) among women receiving 17-α hydroxyprogesterone caproate (17-OHPC) with and without recurrent preterm birth (PTB).Study Design This was a case–control study. We prospectively recruited women with ≥ 1 prior singleton spontaneous PTB <34 weeks receiving 17-OHPC. DNA and RNA were isolated from placentas. RNA abundance (gene expression) and the methylome were analyzed for 84 genes in nitric oxide pathways. Women with recurrent PTB <34 weeks (cases) were compared with those delivering at term (controls). Statistical analysis included multivariable models with Bonferroni's corrected p-values.Results In this study, 17 women met inclusion criteria; 7 preterm cases (delivered at 22.6 ± 2.9 weeks) and 10 term controls (delivered at 38.5 ± 0.8 weeks). Groups had similar PTB history, race/ethnicity, and socioeconomic risk factors for PTB. Twenty-seven nitric oxide genes displayed differential expression (p < 0.05 and q < 0.10) when comparing placentas from preterm cases and term controls; all were downregulated in preterm cases. Eight hundred sixty corresponding CpG sites were differentially methylated between the preterm cases and term controls (Bonferroni's p-value <0.05).Conclusion CpG methylation and gene expression patterns in nitric oxide pathway genes differ among placentas from recurrent PTB compared with term birth following 17-OHPC exposure.
Keywords: 17-α hydroxyprogesterone caproate; epigenetics; gene expression; nitric oxide; recurrent preterm birth